Changing the medication documentation process for discharge: impact on clinical routine and documentation quality—a process analysis - Morath, Benedict; Lampert, Anette; Glaß, Franziska; Metzner, Michael; Haefeli, Walter E.; Seidling, Hanna (European journal of hospital pharmacy, 2021)
Objectives In 2017, an in-house best-practice process for medication documentation was developed and implemented to meet the new German legal requirements concerning the management of patient discharge from the hospital. Because this law regulates the common steps of good discharge practices (eg, specification of discharge mediation documentation), we used its implementation to assess the impact of such a measure on the quality of medication documentation and related workflows in clinical routine. - Methods By observing workflows and interviewing the affected employees, we analysed the medication workflow processes from admission to discharge of seven representative departments of a large university hospital before and early after implementation of a newly defined best-practice process. To investigate the implementation impact, following measures were determined overall and for five key process steps: quality of medication documentation as measured by predefined criteria, the adherence to the best-practice process (range 0%-100%), workload and potential shifts in responsibilities. - Results Already early after implementation, all departments met the legal requirements and the quality of the medication documentation increased from low to high quality in most departments. Mean adherence to the best-practice process was 77% (range 60%-100%) with strictest adherence of 100% in one department. Thereby, the number of process steps and hence, likely also the workload increased in all departments. New tasks were mainly performed by physicians and in one department by pharmacists. - Conclusions The new lawful best-practice process led to a higher quality in medication documentation at the cost of a higher workload for physicians, potentially limiting time for other care tasks. Therefore, it could be important to define areas of the medication documentation process in which physicians could be supported by other professions or new tools facilitating accurate medication documentation as the basis of continuity of care.